(untitled) (INNOVATIVE ECONOMY, 2021)
Voichuk M.V. ETYMOLOGY CONCEPT OF THE “ECONOMIC INCLUSION” IN THE CONTEXT OF CYCLIC DEVELOPMENT OF ECONOMY Purpose. The aim of the article is defining theoretical approaches and conceptual bases to the concept of inclusiveness in the economy in order to form new methodological approaches to the study of economic processes at the meso and micro levels. Methodology of research. The methods generally accepted in economics were used in the course of the research, in particular: monographic, system and structural (to determine the meaning of the concept of economic inclusion in the context of cyclical economic development). Findings. The analysis and systematization of theoretical approaches to the definition of the category “inclusion” in the economy are carried out. It is established that the process of inclusion in the economy is a tool to increase people`s participation in the creation, distribution, and consumption of economic goods. The necessity of distinguishing between the concepts of “inclusive growth” and “inclusive development” on the basis of the theory of economic cycles is substantiated. It is determined that economic inclusion is a tool for achieving the priorities of sustainable economic development. It is proved that the use of inclusion as an operational tool of the sustainable development paradigm is aimed at ensuring long-term and sustainable results of economic development at the micro and meso levels. Originality. The necessity of deepening the scientific discourse of economic inclusion, which requires localization and application of the principles of descending governance, is substantiated. For the first time, it is proposed to make a clear distinction between the processes of inclusive growth and inclusive development, which, in contrast to existing approaches, expands the theoretical and methodological basis for the study of economic inclusion at different levels of the economy. Practical value. The practical significance of the obtained results lies in the possibility of integrating inclusive approaches to development strategies and forming practical tools for inclusive development and supporting inclusive growth of micro and meso economic entities by government agencies and representatives of business structures. Key words: inclusiveness, sustainable development, inclusive growth, inclusive development.